Effect of Additional Sulfide and Thiosulfate on Corrosion of Q235 Carbon Steel in Alkaline Solutions. (15th August 2016) - Quan, Bian Li; Li, Jun Qi; Chen, Chao Yi
Abstract : This paper investigated the effect of additional sulfide and thiosulfate on Q235 carbon steel corrosion in alkaline solutions. Weight loss method, scanning electron microscopy (SEM) equipped with EDS, X-ray photoelectron spectroscopy (XPS), and electrochemical measurements were used in this study to show the corrosion behavior and electrochemistry of Q235 carbon steel. Results indicate that the synergistic corrosion rate of Q235 carbon steel in alkaline solution containing sulfide and thiosulfate is larger than that of sulfide and thiosulfate alone, which could be due to redox reaction of sulfide and thiosulfate. The surface cracks and pitting characteristics of the specimens after corrosion were carefully examined and the corrosion products film is flake grains and defective. The main corrosion products of specimen induced by S 2− and S2 O 3 2 - are FeS, FeS2, Fe3 O4, and FeOOH. The present study shows that the corrosion mechanism of S 2− and S2 O 3 2 - is different for the corrosion of Q235 carbon steel.